Applied Quantum Computing and Cryptography Challenges, Opportunities, and Performance Analysis for Algorithms - Mihailescu, Marius Iulian (Studies in Big Data, 2025)
This book explores the dynamically developing areas of quantum computing and quantum cryptography. The book offers an in-depth examination of the possibilities and difficulties presented by these revolutionary technologies, with the goal of connecting abstract ideas with real-world applications. The book is an extremely helpful resource in the context of the upcoming quantum age. This highlights the importance of creating cryptographic techniques that can withstand the power of quantum computers to protect digital communications and vital infrastructures. This work makes a substantial contribution to the topic of cybersecurity by doing a comprehensive analysis of classical and quantum cryptography approaches, as well as actual implementations and performance evaluations. The book plays a vital role in providing valuable guidance to researchers, practitioners, and policymakers. It offers valuable insights that are necessary for effectively managing the shift towards quantum-secure technology and safeguarding the future security of digital information